EСONOMIC PROBLEMS OF HUNTING PHEASANT BREEDING IN UKRAINE - Фролов, Д. О. (Scientific Progress & Innovations, 2014)
Economic efficiency of the farm depends on maintaining the technology of birds breeding. During the optimization process of the hunting pheasant breeding content in the farm "Skiff" for 3 years we managed to increase the number of chicks from one female 185 %. In the case of maintenance of the hunting pheasant breeding technology on all farms in Ukraine, the number of young chickens increases by 113103. In the recalculation to the cash index, the economic effect for Ukraine as a whole will be more than 13,3 million UAH.